Answer:
for all values
Explanation:
u = (t - 2, 6 - t, - 4)
v = ( - 4, t - 2, 6 - t)
Angle between them, θ = 120°
Use the concept of dot product of two vectors
![\overrightarrow{A}.\overrightarrow{B}=A B Cos\theta](https://img.qammunity.org/2020/formulas/mathematics/college/zjrbsxli3695gcx7donrzpu64cnzvogxdi.png)
Magnitude of u =
![\sqrt{(t-2)^(2)+(6-t)^(2)+(-4)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/college/4nu6htczgugsv8qjpnetd4eda8puqjoqzo.png)
=
![\sqrt{2t^(2)-16t+56}](https://img.qammunity.org/2020/formulas/mathematics/college/oqzegk5gpi4o5aa8se1kei204v1wstbr3p.png)
Magnitude of v =
![\sqrt{(t-2)^(2)+(6-t)^(2)+(-4)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/college/4nu6htczgugsv8qjpnetd4eda8puqjoqzo.png)
=
![\sqrt{2t^(2)-16t+56}](https://img.qammunity.org/2020/formulas/mathematics/college/oqzegk5gpi4o5aa8se1kei204v1wstbr3p.png)
![\overrightarrow{u}.\overrightarrow{v}=-4(t-2)+(6-t)(t-2)-4(6-t)=-t^(2)+8t-28](https://img.qammunity.org/2020/formulas/mathematics/college/25n0ctlojv8kkw2i2ld5ce3bymjh6cle6v.png)
By the formula of dot product of two vectors
![Cos120 = \frac{-t^(2)+8t-28}{\sqrt{2t^(2)-16t+56}* \sqrt{2t^(2)-16t+56}}](https://img.qammunity.org/2020/formulas/mathematics/college/ctrqqegm7y0ce5p5jicfzgtkgtyko5dr0b.png)
![-0.5* {2t^(2)-16t+56} = {-t^(2)+8t-28}}](https://img.qammunity.org/2020/formulas/mathematics/college/6kpse9pnifa1mzd3c0icutdsziwio4gemw.png)
![{-t^(2)+8t-28}} = {-t^(2)+8t-28}}](https://img.qammunity.org/2020/formulas/mathematics/college/xlra0dzx0e2x4k3rpoh3q2bw0j7fxhxcp2.png)
So, for all values of t the angle between these two vectors be 120.